Regeneration of transformer oil under laboratory conditions - Rakhimov, Р.В. (Eurasian Journal of Applied Engineering and Technology (EJAET), 2023)
The author of the article considers the issue of transformer oil regeneration under laboratory conditions using a rotary evaporator. The purpose of the study is to improve the electrical insulation properties by removing excess moisture from the oil composition. The rotary evaporator, working at reduced pressure, heats the oil, removes the moisture contained in the form of sediment or emulsion, thereby increasing the electrical insulation properties of the oil and reducing its oxidizing properties. The test is of a laboratory nature and has a test sample weight of 1 kilogram. During the testing process, a Heidolph rotary evaporator of the Hei-VAP Precision series, manufactured in 2018 (Germany), was used. The test of the sample was carried out on the basis of the road laboratory of the research and production center "ENU-Lab", created in the framework of the state program of industrial and innovative development of the Republic of Kazakhstan. The main results were obtained, namely: the amount of moisture released (W) as a percentage, due to the difference in mass before and after the test of the sample. The results obtained were compared with the requirements of the current regulatory and technical documentation on the territory of the Republic of Kazakhstan. Comparative data allow us to draw conclusions about the need to reduce the moisture content of the transformer oil supplied to the market, by using a rotary evaporator as the main tool to achieve this goal. The results can be used for practical purposes with the creation of industrial-scale installations. Also, with the help of the obtained results, it is possible to indicate the need for the introduction of this technology, in the form of an additional one, at the existing plants for the production of transformer oil.